Nitrogen fertilisation of durum wheat: a case study in Mediterranean area during transition to conservation agriculture - Galieni, Angelica; Stagnari, Fabio; Visioli, Giovanna; Marmiroli, Nelson; Speca, Stefano; Angelozzi, Giovanni; D’Egidio, Sara; Pisante, Michele (Italian Journal of Agronomy, 2016)
Nitrogen (N) nutrition plays a key role for high yields and quality in durum wheat (Triticum turgidum L. subsp. durum (Desf.) Husn); in Mediterranean environments, data regarding N fertilisation management during the transition phase to conservation agriculture (CA) are limited. The aim of this work was to study the effects of N fertiliser forms and rates on yield and some quality traits of durum wheat, during the transition period to CA in Mediterranean areas; moreover, indication on the recommendable N form/rate combinations have been given. Field trials were carried out in south of Italy, during the first two years of transition to CA (from 2010 to 2012) in a durum wheat-based rotation. Following a split-plot design arranged on a randomised complete blocks with three replications, two N forms (main plots) - urea and calcium nitrate - and four N rates (sub-plots) - 50, 100, 150 and 200 kg N ha–1 - plus an un-fertilised Control, were compared. The following parameters were analysed: grain yield, N-input efficiency, grains protein concentration (GPC), total gluten, gluten fractions and minerals concentration in kernels. Calcium nitrate gave the highest yield (4.48 t ha–1), as predicted by the quadratic model, at 146 kg N ha–1, on average. This was particularly noticeable in 2012, when the distribution of rainfall and temperatures regimes as well as residues’ status could have favoured such N-form. These results were confirmed by the observed higher values of all indices describing N-input efficiency. High GPC values (14.8%) were predicted at slightly higher N-rates (173 kg N ha–1, averaging both N forms). In particular, gluten proteins and glutenin/gliadin ratio accrued as the N doses increased, reaching the highest values at 150 kg N ha–1, also positively affecting the quality of durum wheat flour. Iron and zinc concentrations were noticeably increased (38% and 37% on average) by N supply, probably due to the enhanced water use efficiency under CA systems. Principal component analysis summarised properly the obtained results: analysing the N-rates at 150 kg N ha–1, it was confirmed that yields and quality characteristics of durum wheat were optimised in the wettest year (2011) with calcium nitrate. Moreover, the scarce amount of residues characterising the transition phase to CA, requires N application rates not lower than 150 kg ha–1 in order to ensure stable yields and important quality traits. These N rates should be modulated as the accumulation of crop residues increases over time, thanks to long-term effects of CA on soil chemical, physical and biological properties.